2017
DOI: 10.1177/0891988717700509
|View full text |Cite
|
Sign up to set email alerts
|

Late-Life Depression: Modifications of Brain Resting State Activity

Abstract: Late-life depression (LLD) is a common emotional and mental disability in the elderly population characterized by the presence of depressed mood, the loss of interest or pleasure in daily activities, and other depression symptoms. It has a serious effect on the quality of life of elderly individuals and increases their risk of developing physical and mental diseases. It is an important area of research, given the growing elderly population. Brain functional connectivity modifications represent one of the neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 76 publications
0
22
0
Order By: Relevance
“…The functional relevance of our findings remains to be confirmed in future studies. LLD is associated with altered functional connectivity patterns in regions of the sensorimotor network . Specifically, greater functional connectivity within the superior parietal lobe (including the primary somatosensory cortex) has been found in LLD and shown to correlate with overall depressive and somatic symptom severity.…”
Section: Discussionmentioning
confidence: 99%
“…The functional relevance of our findings remains to be confirmed in future studies. LLD is associated with altered functional connectivity patterns in regions of the sensorimotor network . Specifically, greater functional connectivity within the superior parietal lobe (including the primary somatosensory cortex) has been found in LLD and shown to correlate with overall depressive and somatic symptom severity.…”
Section: Discussionmentioning
confidence: 99%
“…However, connectivity between the SN (i.e., anterior insula, dorsal ACC) and the anterior nodes of DMN [ 82 ] as well as between the insula and the amygdala [ 83 ] seems enhanced in depressed individuals when compared with controls and these results are coherent with the more engagement in mentalizing about the self and past autobiographical experiences and focusing on negative thoughts demonstrated in these patients. In our recent study [ 37 ] we showed a significant modification in the left FPN (lFPN) characterized by increased connectivity in the left Superior Parietal Lobule (SPL) and left DLPFC in LLD group ( Figure 4 ). The lFPN is implicated in language and working memory processing [ 84 , 85 ] and the significant modification found in our study could justify some typical cognitive symptoms in LLD, assuming an inability to regulate the activation of an important area for specific cognitive tasks, as the case of working memory, impaired in LLD, MCI, and AD.…”
Section: Late Life Depressionmentioning
confidence: 90%
“…Contrast maps are overimposed on Talairach template (T1 weighted images) in radiological convention. The figures are derived from the following study: [ 37 ].…”
Section: Figurementioning
confidence: 99%
“…While structural alterations reflect the long-term influence of depression, and task-based imaging profiles the altered brain reaction to external stimuli or under specific situations, resting-state fMRI explores the intrinsic changes of brain activity in the state without any influence of external stimuli. Resting-state fMRI studies using the method of independent component analysis has revealed that the default mode network, the frontoparietal network and the sensorimotor network showed abnormal connectivity in LLD patients (12,13). LLD patients also exhibited abnormal local synchronization in various brain areas, as revealed by the measure of regional homogeneity (14).…”
Section: Introductionmentioning
confidence: 99%